2005
DOI: 10.1175/jtech1699.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Millimeter Doppler Radar Echoes to Estimate Vertical Air Velocities in the Fair-Weather Convective Boundary Layer

Abstract: Vertical velocity characteristics of the optically clear convective boundary layer (CBL) are examined by means of profiling airborne radar data collected in the central Great Plains during the International H 2 O Project, May-June 2002 (IHOP 2002. Clear-air echoes are sufficiently strong for the radar, a 95-GHz cloud radar, to detect most of the CBL at a resolution of ϳ30 m. Vertical radar transects across the CBL are remarkably dominated by well-defined plumes of higher reflectivity. These echo plumes occupy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
(51 reference statements)
6
53
0
Order By: Relevance
“…Wilson et al 1994;Martin and Shapiro 2007). Angevine (1997) reports a downward bias in mean UHF profiler vertical velocities up to 0.3 m s −1 in the daytime PBL due to the subsidence of particulate scatterers, and Geerts and Miao 2005 show that insects can actively oppose PBL upward vertical motions. Concentration of insects in the southern Plains peaks in the mid-afternoon and overnight, with minima near sunrise and dusk (Martin and Shapiro 2007).…”
Section: Vertical Motionsmentioning
confidence: 99%
“…Wilson et al 1994;Martin and Shapiro 2007). Angevine (1997) reports a downward bias in mean UHF profiler vertical velocities up to 0.3 m s −1 in the daytime PBL due to the subsidence of particulate scatterers, and Geerts and Miao 2005 show that insects can actively oppose PBL upward vertical motions. Concentration of insects in the southern Plains peaks in the mid-afternoon and overnight, with minima near sunrise and dusk (Martin and Shapiro 2007).…”
Section: Vertical Motionsmentioning
confidence: 99%
“…Russell and Wilson (1997) argued that clear-air echoes at X band were dominated by scattering by insects, a conclusion that is essentially inevitable for the 95-GHz (W band) WCR, where contributions from Bragg scattering are smaller than at X band. The scatterers appear to descend, with a mean speed of ϳ0.55 m s Ϫ1 , with respect to the air in which they are embedded (Geerts and Miao 2005). Geerts and Miao (2005) found that the difference between the vertical air motion and the Doppler velocity increased with increasing vertical velocity.…”
Section: B Ihop Resultsmentioning
confidence: 98%
“…The scatterers appear to descend, with a mean speed of ϳ0.55 m s Ϫ1 , with respect to the air in which they are embedded (Geerts and Miao 2005). Geerts and Miao (2005) found that the difference between the vertical air motion and the Doppler velocity increased with increasing vertical velocity. Thus, the vertical Doppler velocities shown in this section most likely underestimate the vertical air velocity.…”
Section: B Ihop Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Live insects can even actively counteract the vertical motions induced by the atmosphere. (Geerts and Miao, 2005;Chandra et al, 2010) These measured velocity values are therefore more ambiguous than those of the Doppler lidar and the wind profiler.…”
Section: Observations Of Air Motion Aerosols and Biological Scatterementioning
confidence: 99%